A combined DEM–FEM numerical method for Shot Peening parameter optimisation. (January 2015) - Murugaratnam, Kovthaman; Utili, Stefano; Petrinic, Nik
Highlights: A novel combined DEM–FEM method for Shot Peening optimisation is presented. The model provides a rapid method to investigate the effect of the peening parameters. A new algorithm was implemented accounting for impact dependent coefficients of restitution. The minimum area required in the analyses to obtain true residual stresses was determined. Abstract: A numerical modelling approach capable of simulating Shot Peening (SP) processes of industrial interest was developed by combining the Discrete Element Method (DEM) with the Finite Element Method (FEM). In this approach, shot–shot and shot–target interactions as well as the overall shot flow were simulated efficiently using rigid body dynamics. A new algorithm to dynamically adapt the coefficient of restitution (CoR) for repeated impacts of shots on the same spot was implemented in the DEM code to take into account the effect of material hardening. Then, a parametric study was conducted using the Finite Element Method (FEM) to investigate the influence of the SP parameters on the development of residual stresses. Finally, a two-step coupling method is presented to combine the output of DEM simulation with FEM analyses to retrieve the Compressive Residual Stresses (CRS) after multiple impacts with the aim to evaluate the minimum area required to be modelled to realistically capture the field of residual stresses. A series of such coupled analyses were performed to determine the effect of peening angle and the combination of initial velocity and mass flow rate on CRS.